Development and application of testing system for vibration and ride comfort of all-terrain vehicle. (September 2019) - Feng, Yu; Xian, Qu
All-terrain vehicles have a remarkable capacity to handle a variety of irregular pavements, demonstrating its great potential in military domain as well as in the field of sports, entertainment, and so on. For all-terrain vehicles, the ride comfort is the core skill and one of the most important performance parameters. Little researches have been done into the ride comfort of all-terrain vehicle, particularly into the comprehensive ride comfort test and evaluation system. Combing the all-terrain vehicle vibration characteristics with the standards of ISO 2631, ISO 5349, and so on, a hardware testing system was developed for evaluating the all-terrain vehicle ride comfort. At the same time, a software analysis system was also built under the help of the hardware test system, which has been used to test and analyze many all-terrain vehicles. According to the test results and drivers' subjective evaluation, the test system was proved to be reliable, convenient, and able to effectively evaluate the all-terrain vehicle ride comfort, providing the theoretical basis for improving the ride comfort of all-terrain vehicles.